Effectiveness of Care for Child Development Program on the Sensitivity and Responsiveness Skills of Mothers - Bahari Gharehgoz, Ali; Heidarabady, Seifollah; Alizadeh, Hamid; Asgari, Mohammad (Iranian Journal of Child Neurology, 2022)
Abstract Objectives The Present study aimed to analyze the Impact of “Care for Child Development" program on the sensitivity and responsiveness skills of mothers of children who are at risk of developmental delay. Materials & Methods This study is a quasi-experimental research planned in pretest-posttest with experimental and control groups. The statistical population included all mothers with children at risk of developmental delay in Tabriz. 50 mothers were selected through purposive sampling. Then, they were randomly divided into two groups of 25 (one experimental group and one control group). The experimental group received training about the program of “Care for child Development “ in 4 group session, while the control group did not receive the same training . The social-emotional assessment/evaluation measure family profile (SEAM TM family profile) and maternal caregiving quality scale were the research measurement tools. The obtained data were evaluated by analysis of covariance (ANCOVA) and independent t-test using SPSS software version 20. Results There was a significant difference between the experimental and control groups in maternal caregiving quality and responsiveness, provision of appropriate activities, predictable programs, and provision of play environment and safe home (P <0.05). Conclusions The results showed that the ‘care for child development’ program has positive effect on sensitivity and responsiveness skills of mothers of at risk children and could be considered and applied as a practical plan in national health policies.